The Role of Employee Perceptions and Environmental Consciousness in Organizational Performance: Exploring the Moderating Effects of Communication - Ariyanto, Sanusi; Halimahtussakdiah, Halimahtussakdiah; Hidayat, Rizki; Walmashitoh, Suranti (International Journal of Economics Development Research (IJEDR), 2024)
The objective of this study was to analyze the impact of employee perceptions and environmental consciousness on performance, taking into account communication as a moderating factor. The study utilized a questionnaire survey to validate its hypotheses and focused on employees in companies located in Riau, Batam, Medan, and Jakarta. Purposive convenience sampling was used, involving 132 participants. The findings revealed that both perception and environmental consciousness influence performance. Furthermore, communication affected performance directly but did not moderate the relationship between employee perceptions, environmental consciousness, and performance.